Analysis of Return on Investment Associated with Changes in Operational Time in the Construction of the Sigli-Banda Aceh Toll Road - Made Bayu Anggara, I; Darma, Yusria; Mubarak, Mubarak (Riviera Publishing, 2023)
The problem with this research is that the government was late in land acquisition, so that PT. Hutama Karya (Persero) as the concession holder in the implementation of toll road construction is constrained in a number of locations. This study aims to determine the impact of delays in land acquisition and implementation of the construction of the Sigli-Banda Aceh Toll Road on net profit and return on investment at the end of the concession period. This study uses a quantitative method approach. Data analysis techniques use Present Net Value (NPV), Internal Rate of Return (IRR), and sensitivity analysis. The results of the study show that delays of 1, 2, and 3 years have an impact on concessionaires going through cash flow deficit periods of 17, 19, and 20 years and surplus cash flow periods of 23, 21, and 20 years. year, where investment returns occur in the 32nd (2050), 34th (2052) and 36th (2054) years, so that at the end of the concession period, the net profit that can be achieved by the concession holder is with an NPV value of Rp. 9,162,336,077,086, Rp. 6,858,784,951,438 and Rp. 4,680,164,756,915. If there are no delays, then the concessionaire only needs to go through a cash flow deficit period of 16 years and a cash flow surplus period of 24 years, where the return on investment capital occurs in year 30 (2048), so that the net profit that can be obtained by the concessionaire is with an NPV value of Rp. 11,647,590,651,181.